Simulasi Respon Mekanik Komposit Busa Polimer Diperkuat Serat Tkks Dengan Variasi Konsentrasi Al2O3 - Ria Dini Wanti Lubis; Bustami Syam; Safri Gunawan (Rekayasa Material, Manufaktur dan Energi, 2020)
Polymer foam composite reinforced by oil palm empty fruit bunches has been developed and with the addition of variations of Al2O3 (alumina) powder as an alternative engineering material on car bumper beams. The purpose of this study is to obtain the results of a comparison of mechanical responses on the two types of bumper beams obtained from experimental results and dynamic simulations using ANSYS Software. The results of the stress distribution that occurs using ANSYS, for bumper-beam type 1 is 0.14122 MPa, 0.1527 MPa, 0.13427 MPa, and 0.1887 MPa for axis x, y, z, and equivalent stress, respectively. Bumper-beam type 2 stresses that occur on the x, y, z, and equivalent stress is 0.011818 MPa, 0.01137 MPa, 0.018746 MPa, and 0.03718 MPa, respectively. The results can be concluded that the addition of Al2O3 (alumina) powder to the bumper beam composition can improve its mechanical response.